Impact of 5'-amp-activated Protein Kinase on Male Gonad and Spermatozoa Functions - Nguyen, Thi Mong Diep (Frontiers in Cell and Developmental Biology, 2017)
As we already know, the male reproductive system requires less energetic investment than the female one. Nevertheless, energy balance is an important feature for spermatozoa production in the testis and for spermatozoa properties after ejaculation. The 5’-AMP-activated protein kinase, AMPK, is a sensor of cell energy, that regulates many metabolic pathways and that has been recently shown to control spermatozoa quality and functions. It is indeed involved in the regulation of spermatozoa quality through its action on the proliferation of testicular somatic cells (Sertoli and Leydig), on spermatozoa motility and acrosome reaction. It also favors spermatozoa quality through the management of lipid peroxidation and antioxidant enzymes. I review here the most recent data available on the roles of AMPK in vertebrate spermatozoa functions.